Corrosion and cavitation erosion behaviors of the manganese-aluminum-bronze cladding layer prepared by MIG in 3.5% NaCl solution. (June 2022) - Song, Q.N.; Zhang, H.N.; Li, H.L.; Hong, H.; Sun, S.Y.; Xu, N.; Zhang, G.Y.; Bao, Y.F.; Qiao, Y.X.
Abstract: A cladding manganese-aluminum-bronze (MAB) layer was obtained by metal-inert gas welding (MIG) on a cast MAB plate, and its corrosion and cavitation erosion (CE) behaviors in 3.5% NaCl solution were evaluated. The cast MAB was composed of coarse α, β phases and large rosette κ precipitates. A much finer and more homogeneous microstructure was obtained in the cladding layer. The corrosion rate of the cladding layer was 19.35% lower than that of the cast MAB. Much thicker corrosion products and deeper corrosion pits were found on the cast substrate as a result of the dissolution of κ phases and preferential corrosion at β phases. In contrast, the cladding layer underwent uniform and slight corrosion because of the homogeneous microstructure. The CE rate of the cast MAB was 19.17% larger than that of the cladding layer. Mechanical impact was the dominated factor responsible for the CE damage for both the two materials. For the cast MAB, the β phases underwent cleavage fracture under the cavitation stress. Cracks initiated at α/κ phase boundaries and caused the detachment of κ phases. The propagation of long cracks inside the α phases resulted in groove-shaped cavities. The slightly higher CE resistance of the cladding layer was benefited from the microstructure refinement and modestly increased hardness. However, the cladding layer was also severely eroded with many narrow cavities on the surface due to the highest proportion of the soft α phase in the microstructure. Graphical Abstract: A finer and more homogeneous microstructure was obtained in the cladding layer prepared by MIG on a cast MAB. It also possessed higher corrosion and cavitation erosion resistances than the cast MAB. ga1